Business Dynamics : Systems, Thinking and Modeling for a Complex World - John D. Sterman (Irwin & McGraw-Hill, 2000)
Today’s leading authority on the subject of this text is the author, MIT Standish Professor of Management and Director of the System Dynamics Group, John D. Sterman. Sterman’s objective is to explain, in a true textbook format, what system dynamics is, and how it can be successfully applied to solve business and organizational problems. System dynamics is both a currently utilized approach to organizational problem solving at the professional level, and a field of study in business, engineering, and social and physical sciences. The field of system dynamics was created in 1956 under the leadership of MIT Professor Jay W. Forrester to evaluate how alternative policies affect growth, stability, fluctuation, and changing behavior in corporations, cities, and countries. Forrester founded the System Dynamics Program in the Alfred P. Sloan School of Management at MIT. John Sterman is currently Director of the System Dynamics Group at MIT. This text is a summary of the wisdom and knowledge gathered over more than twenty years of research dedicated to the study of practical methods for systems thinking and the dynamic modeling of complex systems. It is well written, easy to understand, and worthy of serious consideration. Table of content: 1.Perspective and process Tools for syestem thinking 3.The dynamics of growth 4.Tools for modeling dynamic systems 5. Instability and oscilation 6. Model Testing